Uncle Bobby's wedding - Brannen, Sarah S. (Little Bee Books, 2020)
Chloe is jealous and sad when her favorite uncle announces that he will be getting married, but as she gets to know Jamie better and becomes involved in planning the wedding, she discovers that she will always be special to Uncle Bobby--and to Uncle Jamie, too. This 2020 edition has all-new illustrations by Lucia Soto.